The Exploration of APOS-based PBL Model to Improve the Students’ Mathematics Problem-Solving Skills - Rahayu, Ratri; Kartono, Kartono; Agoestanto, Arief (FKIP Universitas Lampung, 2024)
Math majors must be excellent problem solvers because problem-solving is the foundation of teaching mathematics. Their problem-solving skills will help them create service initiatives as math teachers. This research investigated how well the APOS-based PBL model enhances students' skills in solving mathematical problems. This quasi-experimental design used a non-equivalent post-test-only control group, which is quantitative. Students at a university in Central Java, Indonesia, participated in the study. Tests of problem-solving skills were useful to collect the data. The results of the study showed that (1) students' problem-solving skills lead to learning completion (71); (2) students taught using a modified PBL model based on APOS theory have a different proportion of learning completeness than students taught using an average class using a direct learning model; (3) students' average problem-solving skills taught using the modified PBL model based on APOS theory are superior to those taught in the average class using a direct learning model; (4) increasing students' problem-solving skills taught using a modified PBL model based on APOS theory is preferable to improving students' skills taught using a direct learning model. This study offers insightful insights into the PBL model's implementation, incorporating APOS theory at every stage. These results suggest that to maximize students' problem-solving skills, consideration of the theory of thinking processes must be given when putting the learning model into practice Keywords: APOS, mathematics, PBL, problem-solving skills.DOI: http://dx.doi.org/10.23960/jpmipa/v25i3.pp1577-1592